Application of central composite design for optimizing and statistical analysis of ultrasound-assisted removal of dyes from aqueous solution - Ahmad, Irfan; Alhedrawie, Dilshad; Jain, Vicky; Kumar, Abhinav; Rekha, M. M.; Kundlas, Mayank; Sunitha, S.; Ray, Subhashree; Shomurotova, Shirin (Frontiers in Environmental Science, 2025)
IntroductionThis research evaluates the potential of nickel ferrite magnetic nanoparticles (NFO) for the ultrasound-assisted removal of rhodamine B (RB) and safranin O (SO) from aqueous media. A central composite design (CCD) within the framework of response surface methodology (RSM) was employed to model, optimize, and analyze the removal process.MethodsMeanwhile, the effects of solution pH (3-11), pollutant concentration (10–50 mg L-1), NFO amount (0.01–0.03 g), and sonication time (10-50 min) were investigated systematically.ResultsUnder optimized conditions determined by CCD (i.e., pH of 8, pollutant concentration of 20 mg L-1, NFO amount of 0.038 g, and sonication time of 16 min), the removal efficiencies for RB and SO were achieved at 95.87% and 92.64%, respectively. The adsorbent characterization using scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), Fourier-transform infrared (FTIR), X-ray diffraction (XRD), vibrating sample magnetometer (VSM), and point of zero charge (pHpzc) analysis confirmed the nanometric particle size, high surface area, superparamagnetic properties, and a pHpzc of 6.3 for NFO. Eluent studies indicated that ethanol provided the highest desorption efficiency, enabling effective regeneration of NFO nanoparticles over multiple cycles without significant loss of performance. Application to real water samples demonstrated the practical applicability of NFO, achieving high removal efficiencies while maintaining structural integrity and magnetic separability.DiscussionThese findings highlight the importance of NFO as a promising, reusable, and efficient adsorbent for the rapid removal of toxic dyes under ultrasonic assistance, contributing to the advancement of sustainable water treatment technologies.